ACCURACY ANALYSIS OF DISTANCE MEASUREMENT USING SONAR ULTRASONIC SENSOR HC-SR04 ON SEVERAL TYPES OF MATERIALS - Rihmi, Mihrobi Khalwatu; Bintoro, Gatut; Rahman, Muhamad Arif; Puspito, Gondo; Muntaha, Ali (Directorate of Research and Community Service (DRPM), 2024)
Sonar is a technology that uses the propagation of sound waves to detect the position of an object. Usually, fishermen use sonar to detect fish locations. The problem is that the price of sonar is still expensive, so not all fishermen can afford to use it. One of the devices that can be developed is the HC-SR04 module. HC-SR04 has simple components, and the price is cheap. The use of HC SR04 is still very minimal, so it is necessary to analyze the accuracy of its distance readings on various objects and conditions. The research was conducted using experimental methods in August-September 2023 at the Fishing Exploitation Laboratory, Faculty of Fisheries and Marine Sciences, Brawijaya University. The distance data generated by HC-SR04 is used to measure ceramic, Styrofoam, and fish. Based on the research results, it is known that ceramic and styrofoam objects have a calculated t value = 0 while the one-tail Critical t = 1.65, which means the average distance produced by the tool is the same as the average distance by manual measurement. Meanwhile, in the t-test, the fish samples obtained a value of t stat = 23.24 and t Critical one-tail = 1.65. This shows that the tool will show distance measurement results that differ from manual measurements. Furthermore, the RMSE value of distance measurements on ceramic and Styrofoam objects obtained an average value of 0, which means the measurements are very accurate. Meanwhile, the average RMSE value for fish objects = 37.67, which means that the tool measurements are inaccurate.